Characteristics of the Translation of Lexical Homonyms Within the Scope of The Languages Being Examined - Shadiyeva Shahnoza Sulaymanovna (Academia One, 2024)
This scholarly inquiry delves into the attributes of translating lexical homonyms within the framework of multilingual communication. The research endeavors to scrutinize the intricacies and difficulties linked to the translation of homonyms, taking into account the linguistic and cultural divergences inherent in distinct languages
Keywords: translating homonyms; lexical homonyms; semantic dimensions; specific words